European Political Cultures Conflict or Convergence? - EATWELL, Roger (Routledge, 1997)
European Political Culture looks at the political cultures of the various countries which make up Europe. The international team of writers address a variety of crucial questions, including- what factors help make nations and states? and how do various groups view each other and Europe? We live in a world of increasing interdependence and uniformity, both political and cultural. While advertising campaigns are increasingly designed to cross national boundaries and products are named for their multi-lingual appeal, Europe remains the cradle of modern nationalism. European Political Culture explores these issues, illustrating the dangers of a movement towards ever-growing union which does not take note of the growing populist resistance to Europe.